Interface design guidelines for visually impaired Learning Management Systems users - Kulpa, Cínthia Costa; Perry, Gabriela Trindade; Amaral, Fernando Gonçalves (InfoDesign, 2021)
This paper describes the process of elaborating a set of 23 guidelines for the design of LMS interfaces, aimed at students with visual impairment. The guidelines were developed in a collaborative and user-centered manner, with the collaboration of 12 students with visual impairment (of different levels), 3 specialists in accessibility and 5 web developers and designers. From the survey of students’ needs, the accessibility specialists generated a navigation protocol for students with low vision, which allowed them to identify their difficulties. From this, the set of guidelines was successively refined in a collaborative manner between accessibility specialists and designers and programmers, resulting in the set presented at the end of this paper. Although most of the guidelines listed in this research are not new in terms of interface design, the fact that they have been grouped around the needs of users with visual impairment is an advance, as it facilitates the use of these guidelines by developers who are not subject matter experts